(untitled) (Colombia Medica, 2022)
Background: To date, there is a lack of published information on the utilization of the Deliberative dialogue methodology and the right to a dignified death in minors under 18 years of age in Colombia and Latin America. Objective: To examine the issue of children and adolescents’ entitlement to a dignified death, including the criteria for exclusion, and to formulate a comprehensive plan for pediatric palliative care. A public policy document will be created with the aim of supporting the implementation of Resolution 825/2018. Methods: Participatory Action Research utilizing a Deliberative dialogue methods that has been adapted based on feminist epistemological principles. Results: The outcome of the exercise was the production of a document containing Public Policy recommendations regarding euthanasia in minors and its submission to the Ministry of Health and Social Protection of Colombia a few days prior to the release of the Resolution regulating the right to a dignified death for this population. Additionally, the conclusions of this event enabled the creation of a guide for the implementation of (Cabildos Ciudadanos) Citizen Council, in which girls, boys, and adolescents are included, trans-disciplinarity is encouraged, and feminist epistemological foundations are explored. Conclusions: The deliberative dialogue method may serve as a cost-efficient alternative to replace or complement participatory approaches utilized in the development of public health guidelines and policies.health guidelines and policies.